Investigation of deep level defects in advanced semiconductor materials and devices - AL Saqri, Noor alhuda Ahmed (2017)
This thesis reports an investigation of deep level defects in narrow bandgap semiconductors, namely GaAs and GaAsN, and wide-gap GaN materials and devices that have potential applications in photovoltaics and betavoltaic microbatteries. Indeed, for such applications it is of paramount importance to determine the characteristics of the defects present in the materials, which will help understand their effects on the quality of the materials and the performance of devices. In particular, the investigation is done on: (i) a set of GaAs (311)A solar cell structures gown by molecular beam epitaxy (MBE); (ii) dilute GaAsN epitaxial layers containing different nitrogen concentrations grown by MBE; and (iii) betavoltaic microbattery based on a GaN p–i–n homojunction structures grown by metal-organic vapour phase epitaxy (MOVPE) technique using current-voltage (I-V), capacitance-voltage (C-V), deep level transient spectroscopy (DLTS), and Laplace DLTS measurements. The results of this study show that the defects affected significantly the electrical properties of different advanced semiconductor structures and devices. In particular, InGaAs Quantum Wires (QWr) Intermediate Band Solar Cells based nanostructures grown by MBE were studied. The DLTS and Laplace DLTS results showed that the efficiency measurements and external quantum efficiency (EQE) at different temperatures correlated with the appearance of defect peaks in QWr devices in the same temperature ranges. Additionally, this thesis reports the effect of a high dose of gamma (γ-) irradiation on MBE grown dilute GaAsN epilayers with nitrogen concentrations ranging from 0.2 to 1.2% with post-irradiation stability. The DLTS measurements revealed that after irradiation the number of traps either decreased, remained constant, or new traps are created depending on the concentration of nitrogen. Moreover, this thesis reports the effect of beta particle irradiation on the electrical properties of a betavoltaic microbattery based on a GaN p–i–n homojunction with 200 nm and 600 nm thicknesses of undoped layer (i-GaN). The experimental studies demonstrate that, only the sample with thinner i-GaN layer shows the creation of new shallow donor traps upon irradiation on the p-side of the p-i-n junction. While the sample with thicker i-GaN is more resistant to irradiation.